Regulation And Implementation Of Chemical Castration Punishment Towards Child Sexual Abuse Perpetrator In Indonesia - Tajudin, Ijud; Shaffa Luthfie, Fadhila; Cahya Yudiana, Teguh (Opción, 2019)
Pro and contra in Indonesian community when the Law No.17/ 2016 about Child Protection has been enacted by Indonesian House of Representative to- gether with government. A fascinating issue has arised in public was about that the perpetrator to child sexual abuse such as rape or sexual harassment will be punished not only in jail for years but also they will get chemical cas- tration punishment as additional punishment. Inspite when the judge pun- ished the suspect with chemical castration punishment, there arised a prob- lem that who will execute chemical castration. Law No. 8/1981 about criminal procedure regulated that prosecutor as executor of conviction, however the prosecutor does not have skill to inoculate chemical castration. The doctors as a professional who have skill to do chemical castration refused to be the executor because chemical castration against an oath doctor. Moreover, the criminal conviction which had legal force must be executed to guarantee legal certainty. By using descriptive qualitative analysis, the results show that Indo- nesia aimed to enacted Law No. 17/2016 are to reduce the level of child sexual abuse, to create a deterrent effect to perpetrators, create a preventive element. The factors that being obstacle to implementing conviction chemical cas- tration punishment towards perpetrator of child abuse in Indonesia is the judicial decision already exist but there is no professional to execute of chemical castration. The Indonesian Doctors Association (IDI) refuses as the executor for carrying out additional punishment of chemical castration because Indonesian Doctors Association argued that doctors are prohibited from using their knowledge and competence for matters that are contrary with humanity. The government should regulate Professional for execute chemical castration, prosecutors as executor have competence to inoculate chemical castration.